Combined assessment of climate change and socio-economic development as drivers of freshwater availability in the South of Portugal - Stigter, Tibor (2013)
A combined assessment of the potential impacts from climate change (CC) and socio-economic development (SED) on water resources is presented for a large aquifer in the south of Portugal, under large pressures from water consuming and contaminating activities. We aim to understand how this may further be aggravated by CC and SED, particularly for agriculture, the largest water consumer in the region. Short-term (2020-2050) and long-term (2070-2100) CC scenarios were developed and used to build aquifer recharge and crop water demand scenarios, using different models and methods to account for uncertainty. SED scenarios were developed using a number of techniques, and discussed at workshops with farmers and institutional stakeholders in the water sector. Groundwater use was quantified for each scenario and then integrated with the CC scenarios. They were run through a calibrated groundwater flow model, to study their individual and joint impacts on water levels and discharge rates into the bordering coastal estuary where relevant freshwater dependent wetlands exist. Recharge scenarios show clearly negative long-term trends, but high uncertainties in the short-term. Scenario SED1 predicting intensification and decline of small farms, considered by stakeholders to be most likely, shows a large drop in agricultural area and water demand. SED2, the most desired scenario, foresees growth and modernization of agriculture, but could be unsustainable in combination with CC. The joint analysis of CC and SED revealed to be challenging but useful. It involved the use of different methods across the border between natural and social sciences, aiming to contribute to transdisciplinary water management.